A kind of insole material based on temperature control capsule and preparation method thereof
By using the EVA and TPU matrix in the insole material, combining functional additives such as foaming agents, silicane coupling agents, and adding sexual tunes and temperature -controlled capsules, the existing insole has poor breathability and insufficient abrasion performance. The problem realizes the coordination and improvement of insole performance and improvement of use efficiency.
Patent Information
- Application Number
- CN202411516091.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing insoles have poor breathability, difficult to balance the wear performance, temperature control and breathability, and insufficient tear resistance and water washing stability, which limits the efficiency of the product.
Adopt EVA and TPUs as the substrates, add foaming agents, silane coupling agents, solid -fat acid zinc, and linkers as functional additives, and the coordinated and coordinated and coordinated and coordinated coordination of the tone agent and temperature -controlled capsules is optimized Essence
The coordination and improvement of insoles, breathable and temperature control, improve the stability of tear resistance and water washing, and significantly improve the efficiency of product use.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insole materials, and in particular to an insole material based on a temperature control capsule and a preparation method thereof. Background Art
[0002] Insoles are widely used in the shoe industry, health care, and special functions; they are generally divided into two modes: application-oriented insoles and market commodity-oriented insoles. Insoles used in the shoe industry are mainly used to match the outsoles and midsoles of shoes to make corresponding shapes; size plates are made according to the lasts or panels, and corresponding shapes are made. However, the existing insoles have poor air permeability, and it is difficult to coordinate and balance the improvement of the product's wear performance, temperature control and air permeability. At the same time, the product's tear resistance and water washing stability are poor, which limits the product's use efficiency. Based on this, the present invention further improves it. Summary of the invention
[0003] In view of the defects of the prior art, the object of the present invention is to provide an insole material based on a temperature control capsule and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a temperature control capsule-based insole material, comprising the following raw materials in parts by weight:
[0006] EVA 45-50 parts, TPU 15-20 parts, property-adjusting agent 8-12 parts, temperature-controlling capsule 5-7 parts, foaming agent 4-6 parts, silane coupling agent 3-4 parts, zinc stearate 2-3 parts, cross-linking agent 1-3 parts;
[0007] The preparation method of the property-adjusting agent is as follows:
[0008] S01: adding nano-mica powder to a sufficient amount of hydrogen peroxide solution, stirring and mixing, then washing with water and drying to obtain dry nano-mica powder; heat-treating the dry nano-mica powder at 210-230° C. for 10-15 min, then cooling to 55° C. at a rate of 2-5° C. / min, and keeping the temperature to obtain heat-treated nano-mica powder;
[0009] S02: Add 1 to 3 parts of citric acid and 2 to 4 parts of dopamine solution to 3 to 5 parts of 5% chitosan solution, and then add 2 to 4 parts of sodium carboxymethyl cellulose, stir and mix thoroughly to obtain a primary conditioning solution;
[0010] S03: immersing the nano mica powder heat-treated in S01 into a first conditioning liquid 3 to 5 times the total weight of the nano mica powder heat-treated in S01, stirring and immersing, and after the immersion is completed, washing with water and drying to obtain a first conditioning nano mica agent;
[0011] S04: The first property-adjusting nano-mica agent and the second property-adjusting liquid are mixed and ball-milled in a weight ratio of 5:3, the ball-milling speed is 1500r / min, the ball-milling is performed for 2h, and after the ball-milling is completed, the mixture is washed with water and dried to obtain a property-adjusting agent;
[0012] The preparation method of the temperature-controlled capsule is as follows:
[0013] S11: melamine and paraformaldehyde are mixed in a weight ratio of 1:4, and then sufficient water and sodium hydroxide are added to adjust the pH to 7.5, and the mixture is reacted at 75-85° C. for 20 minutes, and then terephthalaldehyde in an amount of 5% of the total amount of melamine is added, and the mixture is stirred sufficiently to obtain a paraformaldehyde body;
[0014] S12: immersing the carbon nanotubes in a sufficient amount of silane coupling agent solution, stirring and mixing thoroughly, and then filtering and drying to obtain dry carbon nanotubes;
[0015] S13: 3-5 parts of dried carbon nanotubes, 4-7 parts of divinylbenzene, 3-5 parts of amino silicone oil, 5-8 parts of polyformaldehyde and 0.2-0.5 parts of azobisisobutyronitrile are mixed and stirred thoroughly. After the stirring is completed, the mixture is dried to obtain a temperature-controlled capsule.
[0016] Preferably, the insole material comprises the following raw materials in parts by weight:
[0017] EVA 47.5 parts, TPU 17.5 parts, property-adjusting agent 10 parts, temperature control capsule 6 parts, foaming agent 5 parts, silane coupling agent 3.5 parts, zinc stearate 2.5 parts, cross-linking agent 2 parts.
[0018] Preferably, the cross-linking agent is cross-linking agent DCP; the silane coupling agent is silane coupling agent KH560; and the foaming agent is AC foaming agent.
[0019] Preferably, the mass fraction of the hydrogen peroxide solution is 2-5%; the mass fraction of the dopamine solution is 3-6%.
[0020] Preferably, the stirring speed of the stirring immersion treatment is 450-550 r / min, and the stirring time is 20-30 min.
[0021] Preferably, the second conditioning solution comprises the following raw materials in parts by weight:
[0022] 2~4 parts of nano titanium dioxide, 1~3 parts of 2~5% by mass yttrium nitrate solution, 4~7 parts of Tris-HCl buffer solution with a pH value of 8~9, 3~5 parts of nano zinc oxide whiskers and 1~2 parts of nano silica sol.
[0023] Preferably, the silane coupling agent liquid is prepared by mixing silane coupling agent KH550, ethanol and water in a weight ratio of 2:5:1.
[0024] The present invention also provides a method for preparing an insole material based on a temperature control capsule, comprising the following steps:
[0025] The raw materials were weighed according to their weight proportions, and the raw materials were mixed in an internal mixer at a mixing temperature of 140°C for 10 minutes to obtain a mixed product; the mixed product was vulcanized and formed, with the upper and lower mold plates both at a temperature of 160°C, and molded for 120 seconds. The product was cooled, opened the mold and taken out to obtain an insole material based on a temperature-controlled capsule.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The insole material of the present invention adopts EVA and TPU as the matrix, and adds a foaming agent, a silane coupling agent, zinc stearate, and a cross-linking agent as functional additives, and at the same time adds a property-linking agent and a temperature control capsule as a blending synergist. The two are coordinated and matched to enhance the synergy. The obtained insole material can achieve coordinated improvement in wear, air permeability and temperature control, and the product has significant tear resistance and water washing stability.
[0028] 2. The continuous conditioning agent uses nano mica powder as a base material, stirs and mixes thoroughly in a hydrogen peroxide solution, then washes and dries to obtain dry nano mica powder; the dry nano mica powder is heat treated at 210-230°C for 10-15min, and then cooled to 55°C at a rate of 2-5°C / min, and continuous heat treatment is used to optimize the interlaminar spacing and improve the air permeability of the product. At the same time, the chitosan solution, citric acid, dopamine solution and sodium carboxymethyl cellulose are coordinated to obtain a primary conditioning solution. The chitosan solution in the primary conditioning solution has a capacity-permeability-increasing effect, while sodium carboxymethyl cellulose has a dispersing effect, and citric acid has an acidic active function. The dopamine solution is then coordinated to further enhance the active dispersing effect of the primary conditioning solution, thereby enhancing the active efficiency and interface of the nano mica powder through the coordination between the raw materials of the primary conditioning solution, thereby further improving the functional effect of the nano mica powder in the system, and then the wear and air permeability of the product are coordinated, and the product stability is improved;
[0029] 3. The secondary conditioning liquid adopts nano titanium dioxide, yttrium nitrate solution with a mass fraction of 2-5%, Tris-HCl buffer solution with a pH value of 8-9, nano zinc oxide whiskers and nano silica sol for coordinated formulation. Nano zinc oxide whiskers are used as a whisker-like structure distribution system, and nano zinc oxide whiskers, yttrium nitrate solution, Tris-HCl buffer solution and nano silica sol are coordinated to increase the synergy, thereby further optimizing the coordination and stability of product performance. Yttrium nitrate solution has rare earth interfacial activity. In the alkaline environment of Tris-HCl buffer solution, nano silica sol is coordinated and blended. Nano silica sol is dispersed in the Tris-HCl buffer solution system, and yttrium nitrate solution is coordinated, thereby enhancing the dispersion activity of whisker-like nano zinc oxide whiskers in the secondary conditioning liquid system, and then nano titanium dioxide is coordinated and improved. The obtained secondary conditioning liquid enhances the synergy of the first conditioning nano mica agent through nano zinc oxide whiskers and nano titanium dioxide matrix raw materials, thereby further improving the performance of the product;
[0030] 4. The temperature control capsule uses melamine, polyformaldehyde and terephthalaldehyde to form polyformaldehyde. The polyformaldehyde has multiple active groups, and the carbon nanotubes are coupled and can cooperate with polyformaldehyde, divinylbenzene and other raw materials to achieve better interface bonding in the system. The high specific surface area of the carbon nanotubes can achieve a cooling and temperature regulating effect, and the nano-mica powder has a heat storage and heat preservation effect, so the combination of the two can be adjusted to achieve a temperature control effect. At the same time, the high surface area structure of the carbon nanotubes is matched with the lamellar nano-mica powder, and the coupled carbon nanotubes are used to achieve a hydrophobic function, so that the product can achieve the effect of being breathable and waterproof, and the product's water-resistant stability is more significant. DETAILED DESCRIPTION
[0031] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The insole material based on the temperature control capsule of this embodiment includes the following raw materials in parts by weight:
[0033] EVA 45-50 parts, TPU 15-20 parts, property-adjusting agent 8-12 parts, temperature control capsule 5-7 parts, foaming agent 4-6 parts, silane coupling agent 3-4 parts, zinc stearate 2-3 parts, cross-linking agent 1-3 parts.
[0034] The insole material of this embodiment includes the following raw materials in parts by weight:
[0035] EVA 47.5 parts, TPU 17.5 parts, property-adjusting agent 10 parts, temperature control capsule 6 parts, foaming agent 5 parts, silane coupling agent 3.5 parts, zinc stearate 2.5 parts, cross-linking agent 2 parts.
[0036] The cross-linking agent in this embodiment is cross-linking agent DCP; the silane coupling agent is silane coupling agent KH560; and the foaming agent is AC foaming agent.
[0037] The preparation method of the sex-adjusting agent of this embodiment is:
[0038] S01: adding nano-mica powder to a sufficient amount of hydrogen peroxide solution, stirring and mixing, then washing with water and drying to obtain dry nano-mica powder; heat-treating the dry nano-mica powder at 210-230° C. for 10-15 min, then cooling to 55° C. at a rate of 2-5° C. / min, and keeping the temperature to obtain heat-treated nano-mica powder;
[0039] S02: Add 1 to 3 parts of citric acid and 2 to 4 parts of dopamine solution to 3 to 5 parts of 5% chitosan solution, and then add 2 to 4 parts of sodium carboxymethyl cellulose, stir and mix thoroughly to obtain a primary conditioning solution;
[0040] S03: immersing the nano mica powder heat-treated in S01 into a first conditioning liquid 3 to 5 times the total weight of the nano mica powder heat-treated in S01, stirring and immersing, and after the immersion is completed, washing with water and drying to obtain a first conditioning nano mica agent;
[0041] S04: The first property-adjusting nano-mica agent and the second property-adjusting liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500r / min for 2h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a property-adjusting agent.
[0042] The mass fraction of the hydrogen peroxide solution in this embodiment is 2-5%; the mass fraction of the dopamine solution is 3-6%.
[0043] The stirring speed of the stirring immersion treatment in this embodiment is 450-550 r / min, and the stirring time is 20-30 min.
[0044] The second property adjustment liquid of this embodiment includes the following raw materials in parts by weight:
[0045] 2~4 parts of nano titanium dioxide, 1~3 parts of 2~5% by mass yttrium nitrate solution, 4~7 parts of Tris-HCl buffer solution with a pH value of 8~9, 3~5 parts of nano zinc oxide whiskers and 1~2 parts of nano silica sol.
[0046] The preparation method of the temperature-controlled capsule of this embodiment is as follows:
[0047] S11: melamine and paraformaldehyde are mixed in a weight ratio of 1:4, and then sufficient water and sodium hydroxide are added to adjust the pH to 7.5, and the mixture is reacted at 75-85° C. for 20 minutes, and then terephthalaldehyde in an amount of 5% of the total amount of melamine is added, and the mixture is stirred sufficiently to obtain a paraformaldehyde body;
[0048] S12: immersing the carbon nanotubes in a sufficient amount of silane coupling agent solution, stirring and mixing thoroughly, and then filtering and drying to obtain dry carbon nanotubes;
[0049] S13: 3-5 parts of dried carbon nanotubes, 4-7 parts of divinylbenzene, 3-5 parts of amino silicone oil, 5-8 parts of polyformaldehyde and 0.2-0.5 parts of azobisisobutyronitrile are mixed and stirred thoroughly. After the stirring is completed, the mixture is dried to obtain a temperature-controlled capsule.
[0050] The silane coupling agent liquid of this embodiment is prepared by mixing silane coupling agent KH550, ethanol and water in a weight ratio of 2:5:1.
[0051] A method for preparing an insole material based on a temperature control capsule in this embodiment comprises the following steps:
[0052] The raw materials were weighed according to their weight proportions, and the raw materials were mixed in an internal mixer at a mixing temperature of 140°C for 10 minutes to obtain a mixed product; the mixed product was vulcanized and formed, with the upper and lower mold plates both at a temperature of 160°C, and molded for 120 seconds. The product was cooled, opened the mold and taken out to obtain an insole material based on a temperature-controlled capsule.
[0053] Example 1: A temperature-control capsule-based insole material, comprising the following raw materials in parts by weight:
[0054] EVA 45 parts, TPU 15 parts, property-adjusting agent 8 parts, temperature control capsule 5 parts, foaming agent 4 parts, silane coupling agent 3 parts, zinc stearate 2 parts, cross-linking agent 1 part.
[0055] The cross-linking agent in this embodiment is cross-linking agent DCP; the silane coupling agent is silane coupling agent KH560; and the foaming agent is AC foaming agent.
[0056] The preparation method of the sex-adjusting agent of this embodiment is:
[0057] S01: adding nano-mica powder to a sufficient amount of hydrogen peroxide solution, stirring and mixing, then washing with water and drying to obtain dry nano-mica powder; heat-treating the dry nano-mica powder at 210° C. for 10 min, then cooling to 55° C. at a rate of 2° C. / min, and keeping the temperature to obtain heat-treated nano-mica powder;
[0058] S02: Add 1 part of citric acid and 2 parts of dopamine solution to 3 parts of 5% chitosan solution, and then add 2 parts of sodium carboxymethyl cellulose, stir and mix thoroughly to obtain the primary conditioning solution;
[0059] S03: immersing the nano mica powder heat-treated in S01 into a first property-adjusting liquid 3 times the total weight of the nano mica powder heat-treated in S01, stirring and immersing, and after the immersion is completed, washing with water and drying to obtain a first property-adjusting nano mica agent;
[0060] S04: The first property-adjusting nano-mica agent and the second property-adjusting liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500r / min for 2h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a property-adjusting agent.
[0061] The mass fraction of the hydrogen peroxide solution in this embodiment is 2%; the mass fraction of the dopamine solution is 3%.
[0062] The stirring speed of the stirring immersion treatment in this embodiment is 450 r / min, and the stirring time is 20 min.
[0063] The second property adjustment liquid of this embodiment includes the following raw materials in parts by weight:
[0064] 2 parts of nano titanium dioxide, 1 part of 2% by mass yttrium nitrate solution, 4 parts of Tris-HCl buffer solution with a pH value of 8, 3 parts of nano zinc oxide whiskers and 1 part of nano silica sol.
[0065] The preparation method of the temperature-controlled capsule of this embodiment is as follows:
[0066] S11: melamine and paraformaldehyde are mixed in a weight ratio of 1:4, and then sufficient water and sodium hydroxide are added to adjust the pH to 7.5, and the mixture is reacted at 75° C. for 20 minutes, and then terephthalaldehyde in an amount of 5% of the total amount of melamine is added, and the mixture is stirred sufficiently to obtain a paraformaldehyde body;
[0067] S12: immersing the carbon nanotubes in a sufficient amount of silane coupling agent solution, stirring and mixing thoroughly, and then filtering and drying to obtain dry carbon nanotubes;
[0068] S13: 3 parts of dried carbon nanotubes, 4 parts of divinylbenzene, 3 parts of amino silicone oil, 5 parts of polyformaldehyde and 0.2 parts of azobisisobutyronitrile are mixed and stirred thoroughly. After the stirring is completed, the mixture is dried to obtain a temperature-controlled capsule.
[0069] The silane coupling agent liquid of this embodiment is prepared by mixing silane coupling agent KH550, ethanol and water in a weight ratio of 2:5:1.
[0070] A method for preparing an insole material based on a temperature control capsule in this embodiment comprises the following steps:
[0071] The raw materials were weighed according to their weight proportions, and the raw materials were mixed in an internal mixer at a mixing temperature of 140°C for 10 minutes to obtain a mixed product; the mixed product was vulcanized and formed, with the upper and lower mold plates both at a temperature of 160°C, and molded for 120 seconds. The product was cooled, opened the mold and taken out to obtain an insole material based on a temperature-controlled capsule.
[0072] Example 2: A temperature-control capsule-based insole material, comprising the following raw materials in parts by weight:
[0073] EVA 50 parts, TPU 20 parts, property-adjusting agent 12 parts, temperature control capsule 7 parts, foaming agent 6 parts, silane coupling agent 4 parts, zinc stearate 3 parts, cross-linking agent 3 parts.
[0074] The cross-linking agent in this embodiment is cross-linking agent DCP; the silane coupling agent is silane coupling agent KH560; and the foaming agent is AC foaming agent.
[0075] The preparation method of the sex-adjusting agent of this embodiment is:
[0076] S01: adding nano-mica powder to a sufficient amount of hydrogen peroxide solution, stirring and mixing, then washing with water and drying to obtain dry nano-mica powder; heat-treating the dry nano-mica powder at 230° C. for 15 min, then cooling to 55° C. at a rate of 5° C. / min, and keeping the temperature to obtain heat-treated nano-mica powder;
[0077] S02: Add 3 parts of citric acid and 4 parts of dopamine solution to 5 parts of 5% chitosan solution, and then add 4 parts of sodium carboxymethyl cellulose, stir and mix thoroughly to obtain a primary conditioning solution;
[0078] S03: immersing the nano mica powder heat-treated in S01 into a first property-adjusting liquid 5 times the total weight of the nano mica powder heat-treated in S01, stirring and immersing, and after the immersion is completed, washing with water and drying to obtain a first property-adjusting nano mica agent;
[0079] S04: The first property-adjusting nano-mica agent and the second property-adjusting liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500r / min for 2h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a property-adjusting agent.
[0080] The mass fraction of the hydrogen peroxide solution in this embodiment is 5%; the mass fraction of the dopamine solution is 6%.
[0081] The stirring speed of the stirring immersion treatment in this embodiment is 550 r / min, and the stirring time is 30 min.
[0082] The second property adjustment liquid of this embodiment includes the following raw materials in parts by weight:
[0083] 4 parts of nano titanium dioxide, 3 parts of 5% by mass yttrium nitrate solution, 7 parts of Tris-HCl buffer solution with a pH value of 9, 5 parts of nano zinc oxide whiskers and 2 parts of nano silica sol.
[0084] The preparation method of the temperature-controlled capsule of this embodiment is as follows:
[0085] S11: melamine and paraformaldehyde are mixed in a weight ratio of 1:4, and then sufficient water and sodium hydroxide are added to adjust the pH to 7.5, and the mixture is reacted at 85° C. for 20 minutes, and then terephthalaldehyde in an amount of 5% of the total amount of melamine is added, and the mixture is stirred sufficiently to obtain a paraformaldehyde body;
[0086] S12: immersing the carbon nanotubes in a sufficient amount of silane coupling agent solution, stirring and mixing thoroughly, and then filtering and drying to obtain dry carbon nanotubes;
[0087] S13: 5 parts of dried carbon nanotubes, 7 parts of divinylbenzene, 5 parts of amino silicone oil, 8 parts of polyformaldehyde and 0.5 parts of azobisisobutyronitrile are mixed and stirred thoroughly. After the stirring is completed, the mixture is dried to obtain a temperature-controlled capsule.
[0088] The silane coupling agent liquid of this embodiment is prepared by mixing silane coupling agent KH550, ethanol and water in a weight ratio of 2:5:1.
[0089] A method for preparing an insole material based on a temperature control capsule in this embodiment comprises the following steps:
[0090] The raw materials were weighed according to their weight proportions, and the raw materials were mixed in an internal mixer at a mixing temperature of 140°C for 10 minutes to obtain a mixed product; the mixed product was vulcanized and formed, with the upper and lower mold plates both at a temperature of 160°C, and molded for 120 seconds. The product was cooled, opened the mold and taken out to obtain an insole material based on a temperature-controlled capsule.
[0091] Example 3: A temperature-control capsule-based insole material, comprising the following raw materials in parts by weight:
[0092] EVA 47.5 parts, TPU 17.5 parts, property-adjusting agent 10 parts, temperature control capsule 6 parts, foaming agent 5 parts, silane coupling agent 3.5 parts, zinc stearate 2.5 parts, cross-linking agent 2 parts.
[0093] The cross-linking agent in this embodiment is cross-linking agent DCP; the silane coupling agent is silane coupling agent KH560; and the foaming agent is AC foaming agent.
[0094] The preparation method of the sex-adjusting agent of this embodiment is:
[0095] S01: adding nano-mica powder to a sufficient amount of hydrogen peroxide solution, stirring and mixing, then washing with water and drying to obtain dry nano-mica powder; heat-treating the dry nano-mica powder at 220° C. for 12.5 min, then cooling to 55° C. at a rate of 3.5° C. / min, and keeping the temperature to obtain heat-treated nano-mica powder;
[0096] S02: Add 2 parts of citric acid and 3 parts of dopamine solution to 4 parts of 5% chitosan solution, and then add 3 parts of sodium carboxymethyl cellulose, stir and mix thoroughly to obtain a primary conditioning solution;
[0097] S03: immersing the nano mica powder heat-treated in S01 into a first property-adjusting liquid 4 times the total weight of the nano mica powder heat-treated in S01, stirring and immersing, and after the immersion is completed, washing with water and drying to obtain a first property-adjusting nano mica agent;
[0098] S04: The first property-adjusting nano-mica agent and the second property-adjusting liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500r / min for 2h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a property-adjusting agent.
[0099] The mass fraction of the hydrogen peroxide solution in this embodiment is 3.5%; the mass fraction of the dopamine solution is 4.5%.
[0100] The stirring speed of the stirring immersion treatment in this embodiment is 500 r / min, and the stirring time is 25 min.
[0101] The second property adjustment liquid of this embodiment includes the following raw materials in parts by weight:
[0102] 3 parts of nano titanium dioxide, 2 parts of 3.5% yttrium nitrate solution, 5.5 parts of Tris-HCl buffer solution with a pH value of 8.5, 4 parts of nano zinc oxide whiskers and 1.5 parts of nano silica sol.
[0103] The preparation method of the temperature-controlled capsule of this embodiment is as follows:
[0104] S11: melamine and paraformaldehyde are mixed in a weight ratio of 1:4, and then sufficient water and sodium hydroxide are added to adjust the pH to 7.5, and the mixture is reacted at 80° C. for 20 minutes, and then terephthalaldehyde in an amount of 5% of the total amount of melamine is added, and the mixture is stirred sufficiently to obtain a paraformaldehyde body;
[0105] S12: immersing the carbon nanotubes in a sufficient amount of silane coupling agent solution, stirring and mixing thoroughly, and then filtering and drying to obtain dry carbon nanotubes;
[0106] S13: 4 parts of dried carbon nanotubes, 5.5 parts of divinylbenzene, 4 parts of amino silicone oil, 6.5 parts of polyformaldehyde and 0.35 parts of azobisisobutyronitrile are mixed and stirred thoroughly. After the stirring is completed, the mixture is dried to obtain a temperature-controlled capsule.
[0107] The silane coupling agent liquid of this embodiment is prepared by mixing silane coupling agent KH550, ethanol and water in a weight ratio of 2:5:1.
[0108] A method for preparing an insole material based on a temperature control capsule in this embodiment comprises the following steps:
[0109] The raw materials were weighed according to their weight proportions, and the raw materials were mixed in an internal mixer at a mixing temperature of 140°C for 10 minutes to obtain a mixed product; the mixed product was vulcanized and formed, with the upper and lower mold plates both at a temperature of 160°C, and molded for 120 seconds. The product was cooled, opened the mold and taken out to obtain an insole material based on a temperature-controlled capsule.
[0110] The temperature control range of the products of Examples 1-3 was tested, and the test results are shown in Table 1.
[0111] Test method: Place the sample on a cold plate at 20°C in an incubator, take it out after 5 minutes, detect the temperature of the sample using a temperature sensor, repeat the operation 5 times, take the average value, and get the lower limit of temperature control; Place the sample on a hot plate at 35°C in an incubator, take it out after 5 minutes, detect the temperature of the sample using a temperature sensor, repeat the operation 5 times, take the average value, and get the upper limit of temperature control.
[0112] Table 1 Test results of product temperature control range of Examples 1-3:
[0113]
[0114] It can be seen from Table 1 that the product of Example 3 can achieve a temperature control treatment of 24-28°C, thereby improving the temperature control effect of the insole.
[0115] Comparative Example 1:
[0116] The difference from Example 3 is that no sexual intermediary agent is added.
[0117] Comparative Example 2:
[0118] The difference from Example 3 is that step S01 is not used in the sexually active agent.
[0119] Comparative Example 3:
[0120] The difference from Example 3 is that the first property adjustment liquid treatment is not used in the property adjustment agent.
[0121] Comparative Example 4:
[0122] The difference from Example 3 is that no dopamine solution and sodium carboxymethyl cellulose are added to the first conditioning solution.
[0123] Comparative Example 5:
[0124] The difference from Example 3 is that no secondary property adjusting liquid is used in the property adjusting agent.
[0125] Comparative Example 6:
[0126] The difference from Example 3 is that no temperature control capsule is added.
[0127] Comparative Example 7:
[0128] The difference from Example 3 is that no dried carbon nanotubes are added into the temperature-controlled capsules.
[0129] Comparative Example 8:
[0130] The difference from Example 3 is that no paraformaldehyde is added into the temperature-controlled capsule.
[0131] Comparative Example 9:
[0132] The difference from Example 3 is that the dried carbon nanotubes are not treated with a silane coupling agent solution.
[0133] The products of Examples 1 to 3 and Comparative Examples 1 to 9 were subjected to conventional performance tests. At the same time, the products were treated with a tear strength of 4 N / mm for 5 minutes and then washed with water 20 times to test the tear resistance and water washing stability of the products. The test results are shown in Table 2.
[0134] Table 2 Product performance test results of Examples 1 to 3 and Comparative Examples 1 to 9:
[0135]
[0136] It can be seen from Comparative Examples 1 to 9 and Examples 1 to 3 that the product of Example 3 has excellent wear performance and air permeability on the basis of temperature control performance, and the three can be improved in a coordinated manner. In addition, the product has significant effects on tear resistance and product performance stability under water washing conditions;
[0137] The performance of the product showed a significant deterioration trend when no or no continuous adjusting agent was added to the product. The performance of the product was most significant when the two agents were used in combination.
[0138] The performance of the products tended to deteriorate when the S01 step was not used in the continuous conditioning agent, the first conditioning solution was not used in the continuous conditioning agent, dopamine solution and sodium carboxymethyl cellulose were not added to the first conditioning solution, and the second conditioning solution was not used in the continuous conditioning agent. The performance change trend of the product was more obvious when the second conditioning solution was not used;
[0139] The performance effect of the product is most significant when the first conditioning solution obtained by the method of the present invention is combined with the treatment in step S01 and the treatment with the second conditioning solution.
[0140] When no dried carbon nanotubes were added to the temperature-control capsules, no polyformaldehyde was added to the temperature-control capsules, and the dried carbon nanotubes were not treated with silane coupling agent liquid, the performance of the products tended to deteriorate. Only the temperature-control capsules obtained by the method of the present invention had the most obvious product performance effect.
[0141] Since the secondary conditioning liquid has a significant impact on the performance of the product, further research is conducted on this:
[0142] The secondary conditioning solution includes the following raw materials in parts by weight:
[0143] 3 parts of nano titanium dioxide, 2 parts of 3.5% yttrium nitrate solution, 5.5 parts of Tris-HCl buffer solution with a pH value of 8.5, 4 parts of nano zinc oxide whiskers and 1.5 parts of nano silica sol.
[0144] Experimental Example 1:
[0145] The only difference from Example 3 is that no nano titanium dioxide is added to the secondary conditioning solution.
[0146] Experimental Example 2:
[0147] The only difference from Example 3 is that no yttrium nitrate solution is added to the secondary conditioning solution.
[0148] Experimental Example 3:
[0149] The only difference from Example 3 is that no nano zinc oxide whiskers are added to the secondary conditioning solution.
[0150] Experimental Example 4:
[0151] The only difference from Example 3 is that no Tris-HCl buffer solution is added to the secondary conditioning solution.
[0152] Experimental Example 5:
[0153] The only difference from Example 3 is that no nano silica sol is added to the secondary conditioning solution.
[0154] The products of Experimental Examples 1 to 5 were subjected to conventional performance tests. At the same time, the products were treated with a tear strength of 4 N / mm for 5 minutes and then washed with water 20 times to test the tear resistance and water washing stability of the products. The test results are shown in Table 3.
[0155] Table 3 Product performance test results of Experimental Examples 1 to 5:
[0156]
[0157] It can be seen from Experimental Examples 1-5 that no nano zinc oxide whiskers are added to the secondary conditioning solution. Among the preparation factors of the secondary conditioning solution, the performance of the product deteriorates most significantly, followed by no addition of nano titanium dioxide. At the same time, no yttrium nitrate solution, no Tris-HCl buffer solution, and no nano silica sol are added. The performance of the product tends to deteriorate. Only by using the specific raw materials of the present invention, the performance effect of the product is the most significant. Using other raw materials instead cannot achieve the technical effect of the present invention.
[0158] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0159] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A shoe insole material based on a temperature control capsule, characterized in that: It includes the following raw materials in parts by weight: EVA 45-50 parts, TPU 15-20 parts, property-adjusting agent 8-12 parts, temperature-controlling capsule 5-7 parts, foaming agent 4-6 parts, silane coupling agent 3-4 parts, zinc stearate 2-3 parts, cross-linking agent 1-3 parts; The preparation method of the property-adjusting agent is as follows: S01: adding nano-mica powder to a sufficient amount of hydrogen peroxide solution, stirring and mixing, then washing with water and drying to obtain dry nano-mica powder; heat-treating the dry nano-mica powder at 210-230° C. for 10-15 min, then cooling to 55° C. at a rate of 2-5° C. / min, and keeping the temperature to obtain heat-treated nano-mica powder; S02: By weight, add 1 to 3 parts of citric acid and 2 to 4 parts of dopamine solution to 3 to 5 parts of 5% chitosan solution, and then add 2 to 4 parts of sodium carboxymethyl cellulose, stir and mix thoroughly to obtain a primary conditioning solution; S03: immersing the nano mica powder heat-treated in S01 into a first conditioning liquid 3 to 5 times the total weight of the nano mica powder heat-treated in S01, stirring and immersing, and after the immersion is completed, washing with water and drying to obtain a first conditioning nano mica agent; S04: The first property-adjusting nano-mica agent and the second property-adjusting liquid are mixed and ball-milled in a weight ratio of 5:3, the ball-milling speed is 1500r / min, the ball-milling is performed for 2h, and after the ball-milling is completed, the mixture is washed with water and dried to obtain a property-adjusting agent; The secondary conditioning solution comprises the following raw materials in parts by weight: 2~4 parts of nano titanium dioxide, 1~3 parts of yttrium nitrate solution with a mass fraction of 2~5%, 4~7 parts of Tris-HCl buffer solution with a pH value of 8~9, 3~5 parts of nano zinc oxide whiskers and 1~2 parts of nano silica sol; The preparation method of the temperature-controlled capsule is as follows: S11: melamine and paraformaldehyde are mixed in a weight ratio of 1:4, and then sufficient water and sodium hydroxide are added to adjust the pH to 7.5, and the mixture is reacted at 75-85° C. for 20 minutes, and then terephthalaldehyde in an amount of 5% of the total amount of melamine is added, and the mixture is stirred sufficiently to obtain a paraformaldehyde body; S12: immersing the carbon nanotubes in a sufficient amount of silane coupling agent solution, stirring and mixing thoroughly, and then filtering and drying to obtain dry carbon nanotubes; S13: 3-5 parts of dried carbon nanotubes, 4-7 parts of divinylbenzene, 3-5 parts of amino silicone oil, 5-8 parts of polyformaldehyde and 0.2-0.5 parts of azobisisobutyronitrile are mixed and stirred thoroughly. After the stirring is completed, the mixture is dried to obtain a temperature-controlled capsule.
2. The insole material based on the temperature control capsule according to claim 1, characterized in that: The insole material comprises the following raw materials in parts by weight: EVA 47.5 parts, TPU 17.5 parts, property-adjusting agent 10 parts, temperature control capsule 6 parts, foaming agent 5 parts, silane coupling agent 3.5 parts, zinc stearate 2.5 parts, cross-linking agent 2 parts.
3. The insole material based on the temperature control capsule according to claim 1, characterized in that: The cross-linking agent is cross-linking agent DCP; the silane coupling agent is silane coupling agent KH560; and the foaming agent is AC foaming agent.
4. The insole material based on the temperature control capsule according to claim 1, characterized in that: The mass fraction of the hydrogen peroxide solution is 2-5%; the mass fraction of the dopamine solution is 3-6%.
5. The insole material based on the temperature control capsule according to claim 1, characterized in that: The stirring speed of the stirring immersion treatment is 450-550 r / min, and the stirring time is 20-30 min.
6. The insole material based on the temperature control capsule according to claim 1, characterized in that: The silane coupling agent liquid is prepared by mixing silane coupling agent KH550, ethanol and water in a weight ratio of 2:5:
1.
7. A method for preparing an insole material based on a temperature control capsule, for preparing the insole material based on a temperature control capsule as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials were weighed according to their weight proportions, and the raw materials were mixed in an internal mixer at a mixing temperature of 140°C for 10 minutes to obtain a mixed product; the mixed product was vulcanized and formed, with the upper and lower mold plates both at a temperature of 160°C, and molded for 120 seconds. The product was cooled, opened the mold and taken out to obtain an insole material based on a temperature-controlled capsule.
Citation Information
Patent Citations
Elastomer alloy prepared through melt blending of EVA and TPU as well as composition foaming material thereof
CN110551337A
Preparation method of nano silicon dioxide modified starch glue
CN117165219A